Tourism revenue and economic growth relation in Turkey: Evidence of symmetrical, asymmetrical and the rolling window regressions - Yenişehirlioğlu, Emirhan; Taşar, İzzet; Bayat, Tayfur (Statistical Economic and Social Research and, 2020)
Tourism industry is one of the important determinants of economic growth in the Turkish economy. Tourism industry also comes into prominence as one of the key factors in economic growth due to its foreign currency inflow effect and its multiplier effect being higher compared to other industries. Previous studies show that increase in tourism revenues has a direct positive contribution to economic growth in developed and developing countries. In this study we investigated the 1995-2017 period, tourism income by the method parameter estimates relationship between economic growth in Turkey's economy. Autoregressive distributed lag (ARDL) regression models, and bootstrap rolling window causality parameter tests were used in the empirical analysis. As a result of the empirical analysis, positive contribution to economic growth from the positive component of tourism income in symmetrical regression and asymmetric regression, asymmetric regression was found to be a negative contribution to economic growth from the negative component of tourism income. According to rolling window regression from tourism income to economic growth there is a positive effect between 2010-2015 and negative effect between 2016-2017. © 2020, Statistical Economic and Social Research and. All rights reserved.
Keywords: Asymmetry; Economic growth; Rolling window; Tourism income